Hepatocyte differentiation of human induced pluripotent stem cells is modulated by stearoyl‐CoA desaturase 1 activity. (17th December 2015) - Rahimi, Yaghoub; Mehdizadeh, Amir; Nozad Charoudeh, Hojjatollah; Nouri, Mohammad; Valaei, Kobra; Fayezi, Shabnam; Darabi, Masoud
Abstract : Stearoyl‐CoA desaturase 1 (SCD1) plays important roles in organ development, glucose tolerance, insulin sensitivity, and cancer. Here, we examined the role of SCD1 for the differentiation of human induced pluripotent stem (hiPS) cells to liver cells by using drug inhibition and biochemical experiments. hiPS cells cultured in a pro‐hepatic medium were exposed to an SCD1 inhibitor at various stages throughout differentiation. Liver‐specific markers, specifically α‐fetoprotein, albumin and urea in conditioned medium, and hepatocyte nuclear factor 4 α (HNF4 α ) and cytochrome P450 7A1 (CYP7A1) gene expressions and triglyceride in cellular extracts were analyzed at various development stages. Measures of hepatocyte‐specific function and triglyceride accumulation in later stages were strongly inhibited a minimum of −29% ( P < 0.05) by SCD1 inhibitor in the early stage of hepatic differentiation and effectively reversed (>30%, P < 0.01) by the addition of oleate. The results were also reproducible with human primary mononuclear cells (hPMN). SCD1 inhibitor had no significant effect on liver‐specific markers when it was added in the hepatic maturation stage. However, it strikingly led to higher albumin (1.6‐fold, P = 0.03) and urea (1.9‐fold, P = 0.02) production, and HNF4 α (1.9‐fold, P = 0.02) and CYP7A1 (1.3‐fold, P = 0.03) expression upon incubation during the lineage‐commitment stage. Hepatic differentiation from cultured hiPS cells is sensitive to SCD1 inhibition and this sensitivity is affected by the stage of cellular differentiation. Notably, findings also indicate that this notion can be extended to hPMN. The requirement for SCD1 activity in functional differentiation of hepatocytes may have relevance for human liver disease and metabolic dysregulation. Abstract : Hepatic differentiation from cultured human induced pluripotent stem cells is sensitive to stearoyl‐CoA desaturase 1 (SCD1) inhibition and this sensitivity is affected by the stage of cellular differentiation. The requirement for SCD1 activity in functional differentiation of hepatocytes may have relevance for human liver disease and metabolic dysregulation.